FAFNIR: Strategy and risk reduction in accelerator driven neutron sources for fusion materials irradiation data - Surrey, E; Porton, M; Caballero, A; Davenne, T; Findlay, D; Letchford, A; Thomason, J; Marrow, T; Roberts, S; Seryi, A; Connolly, B; Mummery, P; et al. (Elsevier, 2014)
The need to populate the fusion materials engineering data base has long been recognized, the IFMIF facility being the present proposed neutron source for this purpose. Re-evaluation of the regulatory approach for the EU proposed DEMO device shows that the specification of the neutron source can be reduced with respect to IFMIF, allowing lower risk technology solutions to be considered. The justification for this approach is presented and a description of a proposed facility, FAFNIR, is presented with more detailed discussion of the accelerator and target designs. © 2014 EURATOM/CCFE Fusion Association.